2021
DOI: 10.1038/s41467-021-25677-2
|View full text |Cite
|
Sign up to set email alerts
|

Relief of excited-state antiaromaticity enables the smallest red emitter

Abstract: It is commonly accepted that a large π-conjugated system is necessary to realize low-energy electronic transitions. Contrary to this prevailing notion, we present a new class of light-emitters utilizing a simple benzene core. Among different isomeric forms of diacetylphenylenediamine (DAPA), o- and p-DAPA are fluorescent, whereas m-DAPA is not. Remarkably, p-DAPA is the lightest (FW = 192) molecule displaying red emission. A systematic modification of the DAPA system allows the construction of a library of emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
116
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(118 citation statements)
references
References 65 publications
1
116
1
Order By: Relevance
“…This allows MRSF-TDDFT to overcome the major limitations of conventional TDDFT without the spin-contamination pitfalls of spin flip (SF)-TDDFT, 32 while faithfully reproducing the results of the much more expensive ab initio wave function theories. 29 In a series of studies, 30,31,[33][34][35][36][37][38][39][40][41] it has been demonstrated that the MRSF-TDDFT approach can also yield accurate nonadiabatic coupling matrix elements (NACMEs), 33,35 enabling reliable non-adiabatic molecular dynamics (NAMD) simulations, 40 a topologically correct description of conical intersections, 30,36,39 and accurate values of singlet-triplet gaps. 31,34 In the current letter, by combining standard techniques such as MOM for building a CHP reference and REW for computing X-ray states, we demonstrate that the MRSF-TDDFT is a practical, efficient and very accurate protocol in the computations of X-ray spectroscopy without any major methodological restrictions.…”
Section: Toc Graphicmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows MRSF-TDDFT to overcome the major limitations of conventional TDDFT without the spin-contamination pitfalls of spin flip (SF)-TDDFT, 32 while faithfully reproducing the results of the much more expensive ab initio wave function theories. 29 In a series of studies, 30,31,[33][34][35][36][37][38][39][40][41] it has been demonstrated that the MRSF-TDDFT approach can also yield accurate nonadiabatic coupling matrix elements (NACMEs), 33,35 enabling reliable non-adiabatic molecular dynamics (NAMD) simulations, 40 a topologically correct description of conical intersections, 30,36,39 and accurate values of singlet-triplet gaps. 31,34 In the current letter, by combining standard techniques such as MOM for building a CHP reference and REW for computing X-ray states, we demonstrate that the MRSF-TDDFT is a practical, efficient and very accurate protocol in the computations of X-ray spectroscopy without any major methodological restrictions.…”
Section: Toc Graphicmentioning
confidence: 99%
“…This allows MRSF–TDDFT to overcome the major limitations of conventional TDDFT without the spin-contamination pitfalls of spin flip (SF)–TDDFT, while faithfully reproducing the results of the much more expensive ab initio wave function theories . In a series of studies, ,,, it has been demonstrated that the MRSF–TDDFT approach can also yield accurate nonadiabatic coupling matrix elements (NACMEs), , enabling reliable nonadiabatic molecular dynamics (NAMD) simulations, a topologically correct description of conical intersections, ,, and accurate values of singlet–triplet gaps. , …”
Section: Introductionmentioning
confidence: 99%
“…[19] It has been reported that the HOMO-LUMO gap of benzene is prohibitively large, while the introduction of appropriate electronic controller groups, the frontier molecular orbitals of the parent benzene can be modulated to bring the excitation and emission energy windows to the visible wavelength range. [20] In addition, the ESP was adopted to computationally evaluate how the electron-donating moiety with different substituted positions from the electron-accepting moiety affected the thermally activated delayed fluorescence quantum efficiency and lifetime of the emitter. [21] Clearly, the fine modulation of the basic physical descriptor is an efficient pathway to seek out the most essential factor for determining the optical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as for photophysical properties, these concepts have been employed to explain differences in Stokes shifts of benzoxazole fluorophores, 3 to design chromophores with singlet-triplet energy gaps amenable to singlet-fission photovoltaics, 4 and to design red-light fluorophores based on a simple benzene core. 5 Regarding photochemical reactivity, in turn, the concepts have proven very useful in finding ways to improve the quantum yields of E / Z photoisomerizations that power light-driven molecular motors, 6 in identifying the driving force for excited-state proton transfer 7 and conformational planarization 8 reactions, and in understanding the mechanisms of electron-catalyzed photodissociation processes. 9 …”
Section: Introductionmentioning
confidence: 99%